2012
DOI: 10.1096/fj.11-196378
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of the glutamic acid of the E‐box motif in group B Streptococcus pilus 2a assembly

Abstract: Group B Streptococcus pili are covalently linked structures assembled via a sortase-catalyzed transpeptidation mechanism involving specific residues and motifs. A sequence element containing a conserved glutamic acid, called the E-box, has been described to be involved in pilus formation. Although it is known that the glutamic acid is involved in stabilizing the internal isopeptide bonds, its role in pilus assembly still needs to be investigated. Using site-specific mutagenesis and complementation studies of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Such studies have also shown the presence of either the pilin‐like motif or a linking lysine in basal pilins . The pilins also contain an Ebox motif (YxLxETxAPxGY) with a conserved glutamate, close to C‐terminal region . The Ebox has been shown to be essential for incorporation of ancillary pilins, mediating intramolecular isopeptide bond, and pilus polymerization .…”
Section: Conserved Sequence Motifs In Pilinsmentioning
confidence: 99%
“…Such studies have also shown the presence of either the pilin‐like motif or a linking lysine in basal pilins . The pilins also contain an Ebox motif (YxLxETxAPxGY) with a conserved glutamate, close to C‐terminal region . The Ebox has been shown to be essential for incorporation of ancillary pilins, mediating intramolecular isopeptide bond, and pilus polymerization .…”
Section: Conserved Sequence Motifs In Pilinsmentioning
confidence: 99%
“…To demonstrate the specific contribution in pilus assembly of both the Lys189 in the pilin motif and the IPQTG motif, we used site‐specific mutagenesis and complementation studies. The plasmid (pAM‐BP K189A ) expressing a BP carrying a mutation of the pilin motif lysine residue into alanine and the second plasmid (pAM‐BP ΔIPQTG ) carrying a deletion of the entire IPQTG sorting signal were used to transform the GBS‐KO mutant strain lacking the BP‐2a gene (515ΔBP‐2a) (9, 40). After complementation, the effects of each mutation/deletion on pilus formation were assessed by Western blot analysis, using total proteins extracted from each complemented strain and sera specific for the pilin subunits.…”
Section: Resultsmentioning
confidence: 99%
“…Digestion mixture of trypsin-SrtC1 WT (ratio 1:100) in buffer (25 mM Tris-HCl and 150 mM NaCl) was loaded in a superdex75 10/300 column. Fractions corresponding to the major peaks(7,8,15,16,20,31,40, and 44 kDa) were collected and analyzed by SDS-PAGE. B) SDS-PAGE of the 8 fractions collected by SEC, showing the coelution of the N-terminal region and the sortase core of SrtC1 WT .…”
mentioning
confidence: 99%
“…The activity of the enzyme at different temperatures was determined by incubating the reaction mixture at temperatures ranging from 30 o C to 70 o C. The optimum pH of the enzyme was determined by incubating the assay reaction mixture containing recombinant chitinases using the following buffers (all at a concentration of 0.1 M): sodium acetate (pH values 4 and 5), sodium phosphate (pH values 6 and 7), Tris-HCl (pH values 8 and 9), and glycine-NaOH (pH 10). The optimal pH for enzyme activity was determined by incubating the purified enzyme at different pH values (3)(4)(5)(6)(7)(8)(9) and measuring the activity under standard assay conditions using colloidal chitin as the substrate. To determine the salt-tolerance property of the enzyme, different concentrations of NaCl (0.1-3 M) were used for this purpose.…”
Section: Effects Of Temperature Ph and Nacl Concentration On Chitinmentioning
confidence: 99%